How leadership style, motivation, and workload impact the performance of healthcare workers in Indonesia - Stepvia, Stepvia; Imtiyaaz, Siti Luluiyah; Nurfadhila, Sherly; Essyta, Innge (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Healthcare professionals, including doctors, specialists, and dentists, play a critical role in providing high-quality services to patients. Various factors affect the competencies and performance of these medical personnel, notably leadership style, motivation, and workload. Purpose: To investigate how leadership style, work motivation, and workload influence the performance of healthcare workers in Indonesia in 2024. Method: A quantitative-analytic approach, employing cross-sectional data from a sample of 98 respondents. Results: Leadership style (r=0.59; p < 0.01) and work motivation (r=0.61; p < 0.01) had a significant positive impact on individual performance. Workload (r=0.63; p > 0.05) did not significantly affect performance levels within the scope of this study. Conclusion: Leadership style and work motivation play an important role in enhancing the performance of healthcare workers.